2008
DOI: 10.2165/00002018-200831110-00008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stratification on Adverse Drug Reaction Surveillance

Abstract: Our results indicate that first-pass screening based on observed-to-expected ratios adjusted with stratification may lead to missed signals in ADR surveillance, unless very small strata are avoided. In addition, the improvement in signal detection performance due to routine adjustment for a set of common confounders appears to be smaller than previously assumed. Other approaches to improving signal detection performance such as the development of refined triage criteria may be more promising areas for future r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…However, stratification requires enumeration of all important covariates, which is computationally intractable to use for safety surveillance. Identifying a fixed set of likely covariates for all drugs can help the analysis, but reduces power when dividing the reports across strata that are not correlated with the outcome (4, 8). In addition, stratification is impossible when the reporting systems do not contain reliable measures of the common covariates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, stratification requires enumeration of all important covariates, which is computationally intractable to use for safety surveillance. Identifying a fixed set of likely covariates for all drugs can help the analysis, but reduces power when dividing the reports across strata that are not correlated with the outcome (4, 8). In addition, stratification is impossible when the reporting systems do not contain reliable measures of the common covariates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stratification is impossible when the reporting systems do not contain reliable measures of the common covariates. These factors limit the benefit of applying stratification routinely (8). …”
Section: Introductionmentioning
confidence: 99%
“…It showed that using a MGPS stratified by sex and age reduced the number of vaccine–event pairs highlighted compared with the crude MGPS. On the other hand, Hopstadius raised concern about the routine use of too many stratification factors, which may induce overstratification and lead to missed signals. In addition, after more than 5 years of use in GlaxoSmithKline Vaccine of the MGPS in the setting described earlier, the vaccine–event pairs seemed to have been detected lately and in a small number by the MGPS algorithm compared with the other signal detection methods (instream medical review, literature review, pharmacoepidemiological studies, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Such could be the result of combining several stratification variables or of including excessive number of strata within one variable. 16 This is also the result of the research conducted by Hopstadius et al 11 on the WHO spontaneous reporting database. The authors showed that the observed-to-expected ratios are quite susceptible to the effects of over-stratification and they cautioned that stratification must be carefully designed to avoid very small strata.…”
Section: Discussionmentioning
confidence: 66%